2017
DOI: 10.3198/jpr2016.08.0039crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘YZ01‐1413’ Sugarcane

Abstract: YZ01-1413' (Reg. No. CV-170; PI 678580) sugarcane (a complex hybrid of Saccharum spp.) was developed through cooperative research conducted by Yunnan Sugarcane Research Institute (YSRI), of Yunnan Academy of Agricultural Sciences, and Yunnan Yunzhe Technology Development Co., Ltd. It was released to growers in Yunnan Province, China, on 9 June 2014. YZ01-1413 was selected from the cross 'Yuetang 85-177' × 'ROC10' planned by YSRI and crossed at the Yacheng Sugarcane Breeding Station of Guangzhou Sugar Industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
(4 reference statements)
0
7
0
Order By: Relevance
“…The 14th YRTSV was conducted at six locations in Yunnan Province. This trial differed from the YRTSV reported by Zhao et al (2017) because another testing location, Yuanjiang, was added to the YRTSV to meet the needs of sugar industry in Yuanjiang County (Table 2). The altitude of the six locations ranged from 620.0 m in Yuanjiang to 1652.2 m in Baoshan.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 14th YRTSV was conducted at six locations in Yunnan Province. This trial differed from the YRTSV reported by Zhao et al (2017) because another testing location, Yuanjiang, was added to the YRTSV to meet the needs of sugar industry in Yuanjiang County (Table 2). The altitude of the six locations ranged from 620.0 m in Yuanjiang to 1652.2 m in Baoshan.…”
Section: Methodsmentioning
confidence: 99%
“…After YRTSV, the promising clones that met the following standard, similar to NY/T 1786‐2009 (Chen et al, 2009), were considered for registration in China: an average SC higher than 13.5% (mean value from November to December) as an early‐maturing cultivar or higher than 14.8% (mean value from January to March). They also had to meet one of the condition as compared to the reference cultivars: (i) 5.0% higher‐than‐average cane yield; (ii) <3.0% decrease in cane yield and SC 0.50 (absolute value) higher; (iii) <0.50 (absolute value) decrease in SC with 5.0% higher cane yield; (iv) <3.0% decrease in cane yield and <0.50 (absolute value) decrease in SC with higher disease resistance, drought tolerance, cold tolerance, ratooning ability, self‐trashing, or fiber content; or (v) higher in both cane and sugar yields (Zhao et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al [51] note that Guiyu town in China may be the largest informal recycling site in the world with about 100,000 people engaged informally in recycling activities. Wilmer et al [46] report that in India, the "Cyber City" of Bangalore is threatened by a rapidly increasing amount of e-waste where the informal sector recyclers have caused serious harm to the health of the workers.…”
Section: Introductionmentioning
confidence: 99%